Vertification of the Algirosphaera robusta-Sphaerocalyptra quadridentata (coccolithophores) life-cycle association - Triantaphyllou, M.; Dimiza, M. (Journal of Micropalaeontology, 2003)
Living coccolithophores were collected from eight stations along a transect in the gulf of Korthi (southeastern Andros island, Aegean Sea, Eastern Mediterranean) in August 2001. Samples were collected from 0–120 m water depth to determine the cell density, the species composition and the biogeographical (spatial and vertical) distribution of the coccolithophore biocommunities in coastal marine ecosystems. The studies revealed an impressive heterococcolith–holococcolith combination coccosphere (SEM micrograph) involving the species Algirosphaera robusta and Sphaerocalyptra quadridentata. In addition, a second association was observed by light microscopy. This discovery verifies the suggestions of Kamptner (1941) and provides strong proof on the assignment of these two ‘species’ in a common life cycle, increasing significantly our knowledge of life-cycle pairings ecology.